Underuse of Surveillance Colonoscopy in Patients at Increased Risk of Colorectal Cancer - Murphy, Caitlin C (Am J Gastroenterol, 2015)
OBJECTIVES: Colorectal cancer incidence and mortality have declined over the past two decades, and much of this improvement is attributed to increased use of screening. Approximately 25% of patients who undergo screening colonoscopy have premalignant adenomas that require removal and follow-up colonoscopy. However, there are few studies of the use of surveillance colonoscopy in increased risk patients with previous adenomas. METHODS: We conducted a cross-sectional study to examine factors associated with underuse of surveillance colonoscopy among patients who are at increased risk for colorectal cancer. The study population consisted of patients with previously identified adenomatous polyps and who were due for follow-up colonoscopy. Patients were categorized as attenders (n=100) or non-attenders (n=104) on the basis of completion of follow-up colonoscopy. Telephone surveys assessed the use of surveillance colonoscopy across domains of predisposing patient characteristics, enabling factors, and patient need. Mutlivariable logistic regression was used to identify factors associated with screening completion. RESULTS: Perceived barriers, perceived benefits, social deprivation, and cancer worry were associated with attendance at colonoscopy. Higher benefits (odds ratio (OR) 2.37, 95% confidence interval (CI) 1.04–5.41) and cancer worry (OR 1.73, 95% CI 1.07–2.79) increased the odds of attendance at follow-up colonoscopy, whereas greater barriers (OR 0.49, 95% CI 0.28–0.88) and high social deprivation (≥2; OR 0.09, 95% CI 0.01–0.76) were associated with lower odds. CONCLUSIONS: Our results suggest that multilevel factors contribute to the use of surveillance colonoscopy in higher risk populations, many of which are amenable to intervention. Interventions, such as patient navigation, may help facilitate appropriate use of surveillance colonoscopy.